HUBUNGAN ANTARA DUKUNGAN SOSIAL DAN PENERIMAAN DIRI DENGAN KECEMASAN SELAMA KEHAMILAN DI KABUPATEN BANYUMAS - , Rahmawati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study was to determine the relationship among social support, self-acceptance, and anxiety during pregnancy. Respondents of this study were 99 pregnant women in Banyumas. Sampling method based on purposive sampling with restrictions subject pregnant women (trimester 2 and 3), married (living together), husband who gets a job, the minimun education is junior high school, age 17-34, no history of abortion, pregnancy parity 1-2. The date colection method is summating ratings on a scale of social support, self-acceptance, and anxiety during pregnancy. The value of F test is =18.818 , R = 0.531 (> 0.5) with p = 0.001 (< 0.01), there is significant relationship among social support, self-acceptance, and anxiety during pregnancy. Partially from the t-test, the scale of social support on anxiety during pregnancy obtained value of R = -0.473 and p = 0.000 (< 0.01), there is a negative relationship between social support with anxiety during pregnancy. While selfacceptance to anxiety during pregnancy results obtained value of R = - 0423 and p = 0.007 (< 0.01), there is a negative relationship between selfacceptance with anxiety during pregnancy .